Sentiment and Emotional Analysis of The Public Housing Savings Program (TAPERA) using Orange Data Mining - Fadly, Hawangga Dhiyaul; Jati, Handaru (Politeknik Negeri Batam, 2025)
This study employs a text analysis methodology to assess public perception of the People's Housing Savings Program (TAPERA), by examining 3.078 tweets containing the keyword